(NpO)QÃDINOK (B:s)E (NPOW)QÆSTX (B/s)E - (NkUPR)QÆN(B, (NoLEKSANDR æWANOWI^(B,s)E; (NgORD)QÆÃNKO(B-(NaNDRÆANOWA(B, (Nn(B.,s)E; (NpARHOMOWSXKA(B, (No(B.,s; )Qæ(NWAHNENKO(B, (No(B.,s)E ((NkI)QÇW (B:s)E (NdN)QÆPRO(B,s)E, 1981)
(NwIDATNIJ ROS)QÆJSXKIJ PISXMENNIK(B-(NREALÆST WIKRIWAÃ WADI CARSXKOÇ WOQ^INI(B, (NZMALXOWUÃ POBUT Æ MORALX PROWÆNCÆJNOGO OFÆCERSTWA(B.s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NrOS)QÆJSXKA LÆTERATURAs)E -- (NpOW)QÆSTXs)E